The power of memory in modern Japan - Saaler, Sven, 1968-; Schwentker, Wolfgang (Global Oriental, 2008)
Due to their symbolic and iconographic meanings, expressions of 'collective memory' constitute the mental topography of a society and make a powerful contribution to its cultural, political and social identity. In Japan, the subject of 'memory' has prompted a huge response in recent years. Indeed, it has been and continues to be debated at many levels of Japan's political, social, economic and cultural life. For the historian and social scientist the opportunity to access recorded memories is invariably welcomed as a valuable building block in research and a determinant in establishing balance and perspective. This volume brings together a selection of the most significant research on memory relating to modern Japan. Thematically structured (Politics and International Relations; Memorials, Museums, National Heroes; Popular and Intellectual Representations of Memory; Realms of Memory: Centre and Periphery) the subjects treated include the Nanjing massacre, comfort women, the fate of war monuments, the political use of national memory in post-war Japan and remembering the atomic bomb.